Formative Evaluation for a Healthy Corner Store Initiative in Pitt County, North Carolina: Assessing the Rural Food Environment, Part 1 - Melissa Nelson Laska, PhD, RD; Joseph R. Sharkey, PhD, MPH, RD; Stephanie B. Jilcott Pitts, PhD; Karamie R. Bringolf, MPH; Katherine K. Lawton, MPH; Jared T. McGuirt, MPH; Elizabeth Wall-Bassett, PhD, RD; Jo Morgan, MAEd (Centers for Disease Control and Prevention, 2013)
Introduction Obesity prevalence in the rural United States is higher than in urban or suburban areas, perhaps as a result of the food environment. Because rural residents live farther from supermarkets than their urban- and suburban-dwelling counterparts, they may be more reliant on smaller corner stores that offer fewer healthful food items. Methods As part of a Communities Putting Prevention to Work (CPPW) healthy corner store initiative, we reviewed audit tools in the fall of 2010 to measure the consumer food environment in eastern North Carolina and chose the NEMS-S-Rev (Nutrition Environment Measures Survey-Stores-Revised) to assess 42 food stores. During the spring and summer of 2011, 2 trained graduate assistants audited stores, achieving interrater reliability of at least 80%. NEMS-S-Rev scores of stores in rural versus urban areas were compared. Results Overall, healthful foods were less available and of lower quality in rural areas than in urban areas. NEMS-S-Rev scores indicated that healthful foods were more likely to be available and had similar pricing and quality in rural corner stores than in urban corner stores. Conclusion Food store audit data provided a baseline to implement and evaluate a CPPW healthy corner store initiative in Pitt County. This work serves as a case study, providing lessons learned for engaging community partners when conducting rural food store audits.